PENGARUH AKULTURASI BUDAYA MINANGKABAU PADA ETNIS TIONGHOA DI KOTA PADANG - Rafiq Kurniawan; Shofy Abiyah; Dendi Putra Adriyan; Wita Okta Sari; Mhd Varel Wijaya (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The aim of this research is to describe how the acculturation of Minangkabau culture influences Chinese ethnicity. Cultural acculturation can occur in all levels of society thanks to intercultural communication in society. This research was conducted in Padang City, Pondok Pondok Village, West Padang District. The research method used is a qualitative descriptive method, which describes research based on a description of the actual situation. Informants were determined using a "purposive sampling technique". In data collection techniques through interviews, observation and documentation. The results of this study indicate that the influence of acculturation of Minangkabau culture on Chinese ethnicity can be demonstrated in ethnic Chinese marriages in Padang City by the practice of throwing turmeric rice. Then the ethnic Chinese of the city of Padang also adhere to the Minangkabau philosophy, namely "Dima Bumi Stepped on, Disina Langik Dijjuang" which means they must be able to adapt to their environment, and the bulek philosophy aia dek pambuluah bulek kato deck mufakat means deliberation and consensus.